Purity, Profanity, and Puritanism: the Churching of Women, 1500-1700 - Coster, William (Studies in church history, 1990)
In the past the ceremony of churching was the only means by which, after childbirth, a woman could return to the community of the Church, and indeed to society in general. It is a subject that has received very scant scholarly attention, in spite of the existence of a considerable body of source material concerned with the ceremony, as well as with the ideas and circumstances surrounding it. This material includes the works and debates of theologians and reformers, the survivals of the Church administration, its courts and visitations, biographical material, particularly diaries, and, finally and more unusually, parish registers that record the dates on which churchings occurred. This neglect is all the more surprising in an era that has seen so much emphasis placed on investigations into the historical circumstances of women. This paper will attempt to rectify this situation by utilizing these and the focus point of this ceremony in order to determine the interconnection of religious ideas, with those about sex, motherhood, and women in the early modern period. The theological origins of churching lie ultimately in Leviticus 12, but more directly through the story of the purification of the Virgin in Luke 2. These biblical precedents led to the adoption of such ceremonies into western liturgy around the eleventh century. However, the fact that similar beliefs and rites seem almost universal, perhaps suggests that the introduction of this rite was a response to popular feelings, rather than the imposition of a new ceremony on an increasingly Christianized society. Equally it would seem that the survival of churching through the theological upheavals of the sixteenth century indicates that there continued to be, as Keith Thomas has suggested, within early modern English society, a widespread belief that a woman who had given birth was both unclean and unholy.